The role of arbitration in the resolution of commercial contract disputes under Saudi Law - Almutairi, Abdullah Mushkus (Edelweiss Applied Science and Technology, 2025)
The study examined arbitration as an alternative method of resolving disputes arising from commercial contracts entered into by commercial enterprises for financial gain. The study focused on arbitration as a mechanism to resolve commercial contract disputes. The author adopted a doctrinal approach based on interpreting laws, regulations, and international treaties, and analyzing relevant studies. The collected data for this research appears in a literature study, namely a review of library materials related to the research subject. The study concluded that arbitration is less critical than the judiciary and is not an absolute alternative to it, at least at present. This is due to many disadvantages, mainly because many procedures necessary to achieve justice in court are not followed in arbitration. The study recommended that the law of arbitration explicitly stipulates the arbitrator’s immunity against civil liability for anything he does or omits in complete confidence in his capability as an arbitrator.